Passion Fruit Green Spot Virus Genome Harbors a New Orphan ORF and Highlights the Flexibility of the 5′-End of the RNA2 Segment Across Cileviruses - Ramos-González, Pedro Luis; Santos, Gustavo Francisco dos; Chabi-Jesus, Camila; Harakava, Ricardo; Kitajima, Elliot W.; Freitas-Astúa, Juliana (Frontiers in Microbiology, 2020)
Passion fruit green spot and passion fruit sudden death are two reportedly distinct viral diseases that recurrently affect passion fruit (Passiflora spp.) groves in Brazil. Here we used a systematic approach that interconnects symptoms, transmission electron microscopy, RT-PCR detection assays followed by Sanger sequencing, and high throughput sequencing of the RNA of affected passion fruit plants to gain insights about these diseases. Our data confirmed not only the involvement of cileviruses in these two pathologies, as previously suggested, but also that these viruses belong to the same tentative species: passion fruit green spot virus (PfGSV). Results revealed that PfGSV has a positive-sense RNA genome split into two molecules of approximately 9 kb (RNA1) and 5 kb (RNA2), which share about 50-70% nucleotide sequence identity with other viruses in the genus Cilevirus. Genome sequences of five PfGSV isolates suggest that they have more conserved RNA1 (< 5% of nucleotide sequence variability) compared to RNA2 (up to 7% of variability) molecules. The highest nucleotide sequence divergence among PfGSV isolates and other cileviruses is in the genomic segment covering from the 5’-end of the RNA2 until the 5’-end of the open reading frame (ORF) p61, which includes the ORF p15 and the intergenic region. This genomic stretch also harbors a novel orphan ORF encoding a 13 kDa protein presenting a cysteine-rich domain. High variability of 5’-end of the RNA2 in cileviruses is discussed in an evolutionary context assuming that they share putative common ancestors with unclassified arthropod-infecting single-strand positive RNA viruses, including mosquito-specific viruses of the group Negevirus (clades Nelorpivirus and Sandwavirus), and other viruses in the family Kitaviridae.